Argentometric Titration Apparatus with a Light Emitting Diode‐based Nephelometric Detection System. (1st October 2015) - Bae, Hyun‐Soo; Hwang, Hoon; Eom, In‐Yong
Abstract : End point determination method and examples of titration curve (titration of chloride ion with silver (I) ion) obtained under the stopped flow mode (a) and the continuous flow mode (b). Abstract : A newly revised apparatus for argentometric precipitate titrations was fabricated and evaluated. A light emitting diode was adapted as a solid‐state light source and a syringe pump was used for manipulating titrant both in stopped flow mode and continuous mode. The performance of the two modes was compared in terms of accuracy and precision. The continuous flow mode is much faster and shows generally higher accuracy under given experimental conditions. The patterns of precipitate titration curves were changed with different coagulant concentrations and addition flow rates of titrant. However, end point volumes were not affected by these experimental factors tested here.